Layanan Bimbingan Klasikal Salah Satu Solusi Peningkatan Disiplin Siswa SMPN 1 Selong - Hafadah, Hafadah (Lembaga Yasin AlSys, 2021)
This type of research is Classroom Action Research (CAR) where the target is students who are in the target class. This study aims to determine the improvement of student discipline through the provision of classical guidance services. The research method used is classroom action using two cycles. The subjects of this study were students of class VIII-1 at SMP Negeri 1 Selong as many as 16 people. The data collection tool used is an observation sheet. Data analysis uses data activation techniques about student discipline. The results of this study indicate that the application of classical guidance is effective in improving student discipline.